Obraz bogiń w wersach II 15–54 De raptu Proserpinae Klaudiana (The Portrayal of the Goddesses in Verses II 15–54 of Claudian’s De raptu Proserpinae) - Petry, Martyna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2015)
Claudian’s mythological poem De raptu Proserpinae is almost wholly composed of loosely linked episodes. The disputed verses from his epic, are one of the luxuriant descriptive episodes (ekphrasis) and portray four goddesses tending to the meadow of the Mount Etna. In this paper I’ll try to indicate, that their looks and the symbols depicted on their garments resemble the popular fashion of the contemporary aristocracy and remind of the works of art and motifs characteristic and prevailing in fourth century C.E. Beyond that, not to be overlooked, Claudian simultaneously emulates the divine images that mainly appear in Homer’s and Vergil’s epics as well.